2019
DOI: 10.18502/kss.v3i19.4900
|View full text |Cite
|
Sign up to set email alerts
|

Developing Student’s Oral and Reading Skills Through Reader’s Theatre

Abstract: The ability to speak well in English has always been a challenging task among students from the rural areas. There are various types of materials that have been developed to improve student’s fluency to speak English, and Reader’s Theatre (RT) is one of them. A study was conducted using Readers Theatre to help students improve their oral and reading skills in English in a stress free workshop. The workshop was a combination of language and arts activities that combined language sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…It is recommended that learning English language needs to be encouraged and developed in and out of the classroom through appropriate language activities such as those used in this study. In fact, studies have shown that exposure to language plays such as Readers Theatre play an essential role in improving students' language proficiency (Shanthi et al 2019;Orhan, 2018) because they enable students to learn language effortlessly and effectively (Maroz & Noor Saazai, 2016). When students were allowed to choose language learning activities that were suitable to their needs and interests, learners learned independently and they showed passion and dedication to show better progress in their ability to use English.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is recommended that learning English language needs to be encouraged and developed in and out of the classroom through appropriate language activities such as those used in this study. In fact, studies have shown that exposure to language plays such as Readers Theatre play an essential role in improving students' language proficiency (Shanthi et al 2019;Orhan, 2018) because they enable students to learn language effortlessly and effectively (Maroz & Noor Saazai, 2016). When students were allowed to choose language learning activities that were suitable to their needs and interests, learners learned independently and they showed passion and dedication to show better progress in their ability to use English.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond-the-classroom learning are language activities that encourage language learning outside the classroom (Maros & Mat Saad, 2016). It is said that language activities beyond the classroom promote independent learning (Shanthi et al, 2019) and students can learn a language independently when it becomes crucial for them to use the language to accomplish a set task (Ismail & Shafie, 2019), where learners set goals based on the target to achieve which is the endproduct. In the case of this study the end-product is the ability of students to complete the five activities in English for an audience.…”
Section: Beyond-the-classroom English Activitiesmentioning
confidence: 99%
See 3 more Smart Citations